Recidiva de câncer labial em pacientes atendidos no Hospital Dr. Luiz Antônio (Natal-RN) entre 1997-2004 - Sena, Marina Fernandes de (2009)
Introduction: Cancer of the lip is very common in tropical countries, being noticeable the squamous cell carcinoma as the main histological type. Objective: Evaluate the socialdemographic profile, habits, occupation, clinical characteristics of the cancer lesions and the aftermath of treatment of the patients treated on the Luiz Antônio Hospital (Natal-RN). Design: Retrospective cohort. Methods: We analyzed 181 medical records of patients from the Luiz Antônio Cancer Hospital (Natal-RN) in the period between 1997 and 2004. The statistic evaluation of time between the diagnosis and the relapse or the cure of the patient were done through the Kaplan-Meier method and the comparison of survivor functions were done through the Log-rank test. Later, was estimated the proportional risk model of Cox. Results: The study population were composed by 69,1% males, 95,2% unlettered, the mean age of 66,5 years, 89,0% of smokers and 64,1% had an occupation involving sun exposure. In regard to the clinical characteristics, most lesions were in the lower lip (77,9%), the size of the tumor was smaller than 2 cm (51,8%), 92,6% had localized lesions. Were verified 16,3% of local relapse and 13% of regional. Almost the totally of the cases corresponded to squamous cell carcinoma (97,2%). We observed smaller accumulated probability of not occurrence of local relapse when the base and borders were free of lesions (p=0,041), as well as a smaller probability of regional relapse when the sort of treatment was surgery, associated with other therapeutics modalities (p=0,001). The patients with advanced pathologic stage (p=0,016), treated with surgery associated with other therapeutics modalities (p=0,001) and diameter above 4cm (p=0,019) presented a bigger possibility of any kind of relapse. The multivariable analysis pointed the complex treatments (surgery plus other therapeutics modalities) as a predictor variable for occurrence of new local lesions (p=0,001) and total (p=0,046), besides the age above 70 years to the regional relapse (p=0,050). Conclusion: Cancer of the lip occur in the lower lip, in males, smokers and individuals exposed to Sun light. The relapse was frequent, even being localized and without great consequences to the patient s health. The probability of relapse is related to the size and borders of the lesion and to the histological exam, as well as to the patient s age and complexity of the treatment chosen